EVALUASI KETERSEDIAAN DAN KETEPATAN INFORMASI BUKU TEKS BIOLOGI KELAS XII PADA SUBMATERI GAGAL BERPISAH DAN GEN LETAL - Syahrina, Syahrina; Candramila, Wolly; Wahyuni, Eko Sri (FKIP Universitas Tanjungpura, 2025)
Analysis of the availability and accuracy of concepts in textbooks is very important to clarify unavailable and inaccurate concepts presented in textbooks. This study aims to find the availability and accuracy of the contents of the textbook text in the Nondisjunction and Lethal Gene sub-material in Grade XII Biology textbooks. The analysis focused on the four most commonly used Biology textbooks in 27 high schools in Pontianak City. Qualitative descriptive method with an analysis approach was used. The results of the study showed the availability of important concepts in the nondisjunction and lethal gene sub-material in books A, B and C, there were five available concepts, while in book D there were four available concepts. Overall, one case of oversimplification and three cases of misidentification were found across the four textbooks, particularly in the concepts of the mechanism of nondisjunction in meiosis I and II as well as examples and effects of lethal genes in living organisms.